Laparoscopic Cholecystectomy in a Patient With Situs Inversus Totalis Presenting With Cholelithiasis: A Case Report - He, Tao; Zou, Jieyu; Song, Haiyu; Yi, Bin; Sun, Ke; Yang, Juan; Lei, Tingting; Xu, Lin; Li, Guangkuo (Frontiers in Surgery, 2022)
Laparoscopic cholecystectomy is the standard treatment for cholelithiasis.Situs inversus,a very rare condition,shouldn’t be considered a contraindication for laparoscopic cholecystectomy.We report a case of successful laparoscopic cholecystectomy in a patient with situs inversus totalis,describe the technical advantages, and review the literature.